Profile Of The Use Of Prophylactic Antibiotics For Cesarean Surgery At Hospital “X” Central Jakarta - Nindya Kusumawardhani; Devi Maulina; Anna Uswatun Hasanah Rochjana (Indonesian Journal of Health Science, 2023)
Caesarean section refers to efforts to remove the fetus by performing surgical activities on the abdominal wall and uterus. This surgical activity carries a high risk of postoperative infection. In preventing postoperative infection in cesarean section patients, it is necessary to administer prophylactic antibiotics to prevent postoperative wound infection. Prophylactic administration of antibiotics in surgical patients must be closely monitored to prevent resistance. This study aims to evaluate the use of prophylactic antibiotics in cesarean section patients at a hospital in the Central Jakarta area. The study was conducted for three months, from December 2022 – February 2023. This study used a descriptive method, while data were collected retrospectively. The samples studied in this study were 154 patients. The results obtained in this study showed that the most criteria of patients based on patient age were at the age of 20-35 years as many as 120 patients (77.92%). The type of antibiotic that is often used is Ceftriaxone injection which was carried out in 147 patients (95.45%). Meanwhile, indications of pregnancy that were often found during cesarean section were requests from patients or mothers in 51 patients (33.12%). The use of prophylactic antibiotics based on the hospital formulary is in accordance with the percentage of 100%.